PERSEPSI NILAI PELANGGAN MEMEDIASI PENGARUH KEPERCAYAAN MEREK DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN BERBELANJA ONLINE (STUDI KASUS PADA ZALORA ONLINE SHOP) - Ayu, Dicka Puspita; Sulistyawati, Eka (E-Jurnal Manajemen, 2018)
ABSTRACT The purpose of this study is the role of customer value perception mediate brand trust and quality of service on customer loyalty online shopping (case study on Zalora Online shop). This research was conducted in Zalora Online shop with analytical data path analysis technique. The number of samples obtained by using non-probability sampling method is 150 respondents. Based on the results of the analysis can be known brand trust has a significant positive effect on customer loyalty. Quality of service has a significant positive effect on customer loyalty. Brand trust has a significant positive effect on the perception of customer value. Quality of service has a significant positive effect on the perception of customer value. The perception of customer value has a significant positive effect on customer loyalty. Customer value perceptions mediate the positive impact of brand trust and service quality on customer loyalty shopping at Zalora Online shop.   Keywords: Customer value, brand trust, service quality, customer loyalty